(untitled) (International Journal of Language, Literacy and Translation, 2025)
The institutional training of translators is a relatively new phenomenon beginning in the mid-twentieth century in the institutional training of translators is a relatively new phenomenon beginning in the mid-twentieth century in the West and even later in countries like Iran. Despite the rapid development of Translation Studies in the late twentieth century, translator education did not receive the attention it deserved with trainee translators being trained unsystematically, basically through trial and error. It was only during the recent years that translation scholars and teachers gradually started to address the issue in a more efficient way. The present paper aims to elaborate on the potential of using language corpora in translation classrooms as a means to better help the trainee translators acquire the skills and competencies they need to enter the professional translation market. It further explains the potential of corpora as a resource for translation teachers. Finally, the article proposes a method to archive students’ translations in the form of a parallel corpus and further elaborates on the benefits of using the respective corpus.